Coronary flow evaluation in heart transplant patients compared to healthy controls documents the inadequacy of the coronary flow velocity reserve metric. (25th November 2020) - Cecere, A; Kerkhof, P.L.M; Angelini, A; Gambino, A; Fraiese, A; Bottio, T; Osto, E; Famoso, G; Fedrigo, M; Giacomin, E; Montisci, R; Iliceto, S; et al.
Abstract: Background: Coronary microvasculopathy has impact on prognosis in heart transplantation (HT). Distinct contributions by functional or structural alterations of coronary microcirculation in HT and their prognostic role have not been fully elucidated. Purpose: We aimed to identify the mechanisms of coronary microvascular impairment in HT and their possible prognostic implications by applying a comprehensive analysis in a comparative study. Methods: Included were 134 patients, surviving at least 5 years, with normal systolic function and no evidence of allograft vasculopathy or symptoms/signs of rejection. To permit comparison, 50 healthy volunteers without cardiovascular diseases, and matched for age and sex, served as controls. All underwent echocardiographic evaluation of microvascular function by the assessment of rest and hyperemic diastolic peak blood velocity (DPVr and DPVh). These paired data enable calculation of coronary flow velocity reserve (CFVR) and its inherent companion that is based on the quadratic mean: CFVRC = √(DPVr) 2 + (DPVh) 2 . Additionally, basal and hyperemic coronary microvascular resistance (BMR and HMR) were estimated. A CFVR ≤2.5 was considered abnormal; the median value of DPVh (75 cm/s) and CFVRC (80 cm/s) were selected as cut-offs to classify patients. Results: HT patients can be assigned to four groups, based on their CFVR and DPVh (Figure A): group 1 (n=32), discordant with preserved CFVR (3.1±0.4); group 2 (n=60), concordant with preserved CFVR (3.4±0.5); group 3 (n=31), concordant with impaired CFVR (1.8±0.3) and group 4 (n=11), discordant with impaired CFVR (2.0±0.2). Group 3 represents the structural microvascular remodeling with high HMR, while group 4 represents the functional remodeling with low BMR. Intriguingly, group 1 showed lower DPVr (p<0.0001) and lower DPVh (p<0.0001) than controls (Figure B, upper panel) with lower CFVR (p<0.0001), even if normal, and lower CFVRC (p<0.0001) than controls (Figure B, lower panel). Moreover, both BMR and HMR were higher in group 1 than in controls (5.3±1 vs 4.4±1.2, p=0.001 and 1.5±0.3 vs 1.1±0.2, p<0.0001, respectively), suggesting structural microvascular remodeling. Conversely, group 2 was comparable with controls (Figure B). Clinical characteristics of the different groups are shown in the Table. 13/32 (40.6%) patients in group 1 died in a follow up of 28 years and mortality rate was comparable to group 3 (14/31, 45.2%). However, CFVRC was <80 cm/s in all 13 deaths in group 1, yet being characterized by preserved CFVR (Figure C). Conclusions: A normal CFVR could hide detection of microvascular damage with high flow resistance and low flow velocities at rest. This microvasculopathy seems to be secondary to factors unrelated to HT (i.e., less rejections and more often diabetes). Being a dimensionless ratio, CFVR may miss some deaths, yet captured by CFVRC. Thus, the combined use of CFVR and CFVRC provides more complete clinical information on coronary microvasculopathy in HT. Funding Acknowledgement: Type of funding source: None